THE EFFECT OF ATTACHMENT TO PARENTS TOWARDS ACADEMIC SELF-EFFICACY IN EARLY ADOLESCENTS - Ellenia Fitriana Dewi; Duta Nurdibyanandaru (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Adolescence is a transition period from childhood to adulthood. Adolescents tend to experience a significant transition within themselves whether from physical, cognitive, or socio-emotional. This study aims to determine whether there is an effect of attachment on self-efficacy in early adolescents. This study is conducted on early adolescents with an age range of 12 years to 15 years amounted to 275 children. Based on the analysis result shows the F value of 23.312 with a significance value of 0 <0.05 indicates that there is an influence between attachment to parents on academic self-efficacy in early adolescents. The regression similarity obtained shows a positive influence. Thereby, it can be concluded that the higher the level of attachment to parents, the higher the level of academic self-efficacy possessed by the adolescents.